The Impact of Strategic Leadership on Organizational Performance in Modern Enterprises - Mohammed Ali Mohammed Abdulrahmn Abdullah; Gustian Djuanda (Business Management, 2026)
Strategic leadership has become a critical determinant of organizational success in today’s dynamic and competitive business environment. This study explores the role of strategic leadership in enhancing organizational performance through effective decision-making, innovation, and adaptability. Using a qualitative approach based on secondary data from recent literature and case-based insights, the research identifies key mechanisms linking leadership strategies with performance outcomes. The findings indicate that organizations led by strategic leaders demonstrate higher efficiency, stronger employee engagement, and improved long-term competitiveness. The study concludes that strategic leadership is not merely a managerial function but a fundamental driver of sustainable organizational growth.